Intensification of the development of private international law of the European Union - Babkina, Elena V. (Journal of the Belarusian State University. International Relations, 2018)
To define the main steps and the methods of the europeanisation of private international law, to find out its pros and cons and to propose possible directions for the application of the European Union experience in the practice of the Eurasian Economic Union are the objectives that the author of the present article set for herself. The positive experience of the transnationalization of sources of private international law can also be used by the Eurasian Economic Union.
Keywords: private international law; europeanisation; the European Union; regional unification; sources of law